Fascination and enmity Russia and Germany as entangled histories, 1914-1945 - David-Fox, Michael 1965-; Holquist, Peter 1964-; Martin, Alexander (Pitt series in Russian and East European studies, 2012)
Introduction: Entangled Histories in the Age of Extremes / Michael David-Fox -- "A Belgium of Our Own" : The Sack of Russian Kalisz, August 1914 / Laura Engelstein -- United by Barbed Wire : Russian POWs in Germany, National Stereotypes, and International Relations, 1914-1922 / Oksana Nagornaya -- Iron Revolutionaries and Salon Socialists : Bolsheviks and German Communists in the 1920s and 1930s / Bert Hoppe -- Back from the USSR : The Anti-Comintern's Publications on Soviet Russia in Nazi Germany, 1935-1941 / Jan C. Behrends -- Return to Soviet Russia : Edwin Erich Dwinger and the Narratives of Barbarossa / Peter Fritzsche -- "The Diaries of Fritzes and the Letters of Gretchens" : Personal Writings from the German-Soviet War and Their Readers / Jochen Hellbeck -- Ehrenburg and Grossman : Two Cosmopolitan Jewish Writers Reflect on Nazi Germany at War / Katerina Clark -- The Intelligentsia Meets the Enemy : Educated Soviet Officers in Defeated Germany, 1945 / Oleg Budnitskii -- Mortal Embrace : Germans and (Soviet) Russians in the First Half of the Twentieth Century / Dietrich Beyrau